Envolvente arquitectónica: un espacio para la sostenibilidad (2017)
The article studies the architectural envelopes and their importance in urban and architectural sustainability. It briefly reviews the historical evolution that, thanks to the discovery of oil in the twentieth century, put aside the passive bioclimatic techniques that were developed by the vernacular architecture of all continents. The aim of the article is to highlight the importance of the architectural envelope in terms of the habitability, based on three variables: natural lighting, materials and energy efficiency. As a methodology a systematic review of two types of documents was made: i) those concerning the participation of architecture and the city in the phenomenon of global warming; and ii) those linked to the contemporary concept of architectural envelope. It is concluded that the envelope should be designed with rigor and detail, to contribute to the current mitigation objectives of global warming.